Cross-Border Collaboration: India's UPI Success Story in Indonesia (A CASE STUDY ON Unified Payments System) - Anand, Sahil; Sanchayita, Shubh; Pandey, Mayank Kumar; Suresh, Varshini; M, Gayathri; Siyas, Mohammed; Sahdev, Supriya Lamba; Chidera, Agharany Gift; Natanel, Natanael (AIBPM Publisher, 2024)
This research paper delves into the successful introduction of the Unified Payments Interface (UPI) in the Indonesian market, with a primary focus on crucial elements such as the India-Indonesia memorandum of understanding (MoU), technology transfer, the impact of the 5G spectrum, credit generation, and quantitative analysis through surveys. A notable aspect of this study is examining the current technology transfer process in UPI implementation alongside previous instances, shedding light on the evolution of knowledge transfer methodologies. The effectiveness of the India-Indonesia MoU in facilitating UPI adoption reflects the dedication of both nations. The research investigates how India's expertise in UPI is customized to meet Indonesia's specific needs, historically and in the present. Furthermore, as 5G technology gains prominence, this paper assesses its influence on the efficiency and security of UPI. The study also evaluates UPI's role in promoting credit generation, thereby contributing to financial inclusion and economic growth. The research measures user sentiments, adoption rates, and transaction trends using a multifaceted approach involving surveys and quantitative data analysis. The findings provide valuable insights for policy development, the refinement of technology transfer strategies, and the sustainable growth of digital payment systems in Indonesia and similar emerging markets